Human Resources In Healthcare - Fried, Bruce J. (Health Administration Press, 2012)
This book presents the techniques and practices behind effectively managing people the healthcare industry s most important asset. It provides the concepts and practical tools necessary for meeting the unique challenge of managing healthcare employees.